Hemorrhoids: A comprehensive Review of Etiology, Pathophysiology, Risk Factor and Treatment Option - Akash Ramnayan, Yadav; Kher, Jimisha; Das Mandal, Snigdha (Archives of Advances in Biosciences, 2024)
Context: One of the most prevalent anorectal illnesses is hemorrhoids, and it has placed a formidable medical and social burden on millions worldwide. Evidence Acquisition: The exact etiology of hemorrhoids is still unclear, but it is related to various factors such as dietary irregularities, constipation, obesity, pregnancy, and a sedentary lifestyle. The pathophysiology of hemorrhoids consists of inappropriate dilatation and distortion with destructive changes in vascular channels that support the connective tissue of the anal cushion. Results: Classification is based on the region and level of usual prolapse occurrence; there are internal, external, and mixed types. The risk factors for hemorrhoids include obesity, constipation, pregnancy, and a sedentary lifestyle. The symptoms vary from rectal bleeding and pain to itching, swelling, and discomfort. Regarding treatment, both non-surgical and operative care options are available, including topical and oral medications, lifestyle modifications, and herbal remedies. Conclusion: A complete treatment approach should incorporate a combination of natural therapeutic options alongside allopathic drug therapies to enhance the quality of life for individuals with hemorrhoids.